Structural change of palm oil price data - Lalang Buana; Ahmad Mahir Razali; Zainodin Haji Jubok (Universiti Kebangsaan Malaysia, 1997)
The changes on the vegetables oil trading environment might change the foundation of palm oil pricing and induce a structural change to the price model. Failing to take it account the structural change in a data series might lead to misspecification of the actual model. This study, however, showed that structural change was not present in the monthly, January 1983 to July 1995, palm oil price, but it was present on the unconditional variance. The underlying model of this series was ARIMA (3, 1, 0) with ARCH (1). The critical change of the unconditional variance took place in April 1989.